Simulation of the Biomass and Lipid Production Process from Parachlorella Sp. - Laura F. Pineda; Jorge Rene Silva; Harvey A. Milquez-Sanabria; Dionisio Malagon-Romero (Chemical Engineering Transactions)
Microalgae are a renewable source of biomass for the production of third-generation biofuels that have aroused great interest worldwide because of their rapid growth and ability to fix atmospheric CO2. Additionally, they are capable of accumulating oil in proportions that can exceed 60% of the dry weight, which makes them attractive for biodiesel production. This project aims to evaluate the simulation of the biomass and oil production process using the alga Parachlorella sp. via ASPEN software. The simulation is based on the fixation of CO2 by algae, which, via their cellular metabolism, transforms it into oil, which is then extracted and transesterified into biodiesel. The simulation demonstrated significant biomass growth, since a mass flow of 1000 kg/h of Parachlorella sp. was entered and 336.435 kg/h of biomass was produced, taking into account the necessary nutrients such as water, CO2, oxygen, hydrogen, and carbon sources and a nitrogen source. In addition, a stoichiometric reaction for the conversion of CO2 into tripalmitic oil was generated, resulting in 224.809 kg/h CO2. Through this simulation, a new perspective of decarbonization, biomass generation and, in some cases, biofuels can be developed.